Jean-Christophe Journey's End - Rolland, Romain, 1866-1944; Cannan, Gilbert, 1884-1955 (Salt Lake City, UT : Project Gutenberg, 2005)
"Jean-Christophe Journey's End" by Romain Rolland is the final three volumes of a novel sequence published between 1904 and 1912. This concluding section follows Jean-Christophe Krafft, a musical genius of German heritage living in France, through the latter stages of his tumultuous life. After enduring hardships, spiritual struggles, and forced exile due to conflicts with authority, he seeks peace in Switzerland before a triumphant return to Paris. The work blends personal drama with reflections on music, society, and international understanding. (This is an automatically generated summary.)
Love and Friendship -- The Burning Bush -- The New Dawn.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Jean-Christophe
Release date is 2005-04-01
Produced by Charles Aldarondo, Tiffany Vergon, Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Psychological fiction; Composers -- Fiction; Europe -- Fiction; Epic literature; French fiction -- Translations into English; Musicians -- Fiction